‘Sailing to the Island of the Gods’: Bugis migration in Bali island - HUSAIN, B.; KHUSYAIRI, A.; SAMIDI, S. (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The Bugis migration in the Indonesian archipelago, and even outside of the country, has a lengthy history. By referring to numerous sources, it can be estimated that the Bugis people have been present in Bali since the mid-17th Century. Political and economic issues are two important factors for migrating. As an ethnic group with strong faith and tradition, they have been capable of maintaining their traditions. However, when they live with Balinese who also adhere to their religion and custom, they must adapt. Though the Bugis migration community in Bali has maintained some aspects of its identity. RESUMEN La migración de Bugis en el archipiélago indonesio, e incluso fuera del país, tiene una larga historia. Al referirse a numerosas fuentes, se puede estimar que la gente Bugis ha estado presente en Bali desde mediados del siglo XVII. Las problematicas políticas y económicas son dos factores importantes para hacer la migración. Como grupo étnico con fuerte fe y tradición, han sido capaces de mantener sus tradiciones. Sin embargo, cuando viven con balineses que también se adhieren a su religión y costumbres, deben adaptarse. Aunque la comunidad de migración de Bugis en Bali ha mantenido algunos aspectos de su identidad.